ThIRST: Targeted IRrigation Support Tool for sustainable coffee production - Nguyen, Kien Tri; Craparo, Alessandro; Nguyen, Phuong Minh; Turreira-García, Nerea; Talsma, Tiffany; Deniau, Aline; Bossolasco, Laurent; Le, Trung Dang; Bosselmann, Aske Skovmand (Frontiers in Sustainable Food Systems, 2023)
A grand challenge under climate change is sustainable water management, particularly in intensively farmed areas. This paper draws on the case of Robusta coffee farming in the Central Highlands of Vietnam to illustrate a water saving innovative tool that supports high productivity and sustainable farming. The Central Highlands of Vietnam is an important Robusta coffee growing region. However, the region is facing climate change impacts from rising temperatures and irregular rainfall, while Vietnamese coffee farmers predominantly rely on irrigation from heavily depleted aquifers. To continue productive and sustainable growth, this system requires an innovative approach to meet this hydrological challenge. Here we present a user-friendly tool, which aims to support coffee farmers' irrigation decisions, through the Targeted Irrigation Support Tool or ThIRST. ThIRST combines seasonal forecasts, on-farm metrics, and farmer's expertise. Despite low smartphone usage for farming advisory, theOur results show the tool allows coffee farmers to continually achieve water-use efficiency and adapt to climate variability by combining innovative seasonal forecasting with current biophysical metrics to guide irrigation practices. The tool has been functioning in the developed smartphone app (rtWork) app for 18 months and is currently used by 10 active famers in this initial stage. Involving farmers in the design, production and evaluation of climate services can improve the trust and uptake of agroadvisories and the way this information is communicated.